The COVID Season: U.S. Collegiate Esports Programs' Material Challenges and Opportunities During the 2020–21 Pandemic. Issue 2 (March 2023) - Cote, Amanda C.; Can, Onder; Foxman, Maxwell; Harris, Brandon C.; Hansen, Jared; Rahman, Md Waseq Ur; Fickle, Tara
During the COVID-19 pandemic, universities were among the first institutions to shift to an online model. As they did so, nascent collegiate esports program lost access to campus spaces and in-person connections, potentially destabilizing this rising industry. Conversely, universities also worked to provide students remote access to resources, and many components of esports already occur online. Therefore, collegiate esports may have adjusted to distancing measures, potentially strengthening their footholds on US campuses. This paper draws on in-depth interviews with collegiate esports players, student employees, program directors, and administrators to address different programs' reactions to the pandemic, specifically the challenges and opportunities they faced. Overall, interviews reveal how COVID-19 shifted the understandings of and practices around gaming and esports, highlighted the intermittent relationship of online and offline spheres, and presented various possibilities and challenges for different stakeholders during the global pandemic.